Implementation of Levels of Inquiry Model in Improving Students' HOTS on Fluid Material - Tia Kuraesin; Lina Aviyanti; Harun Imansyah; Amalia Weka Gani (Jurnal Impresi Indonesia, 2024)
This research is motivated by the low level of students' higher order thinking skills (HOTS) in physics. The purpose of this study is to determine how the application of Levels of Inquiry (LoI) learning model in improving students' HOTS. The research design used was a quasi-experiment involving grade XI students in one of the high schools in Bandung City with a research sample of 35 students in the experimental class and 25 students in the control class. The instruments used in this study were higher order thinking skills test in the form of two-level multiple choices for fluid material and observation sheet of learning model implementation. Data analysis techniques include N-Gain, hypothesis testing and effect size. The results of the analysis showed that the application of the LoI learning model in the experimental class was in the excellent category and could improve students' HOTS in the moderate category with an N-gain value of 0.53. In the control class, the application of the conventional learning model can improve students' HOTS in the low category with an N-gain score of 0.18. In addition, the analysis of the Mann-Whitney test results showed that there was a significant difference in students' HOTS between the experimental group and the control group with an effect size in the very large category. This research proves that the application of the LoI learning model is effective in improving students' HOTS in fluid materials.